Early detection of left ventricular diastolic dysfunction using conventional and speckle tracking echocardiography in a large animal model of metabolic dysfunction - Mark M. P. van den Dorpel; Ilkka Heinonen; Sanne M. Snelder; Hendrik J. Vos; Oana Sorop; Ron T. van Domburg; Daphne Merkus; Dirk J. Duncker; Bas M. van Dalen (Springer Netherlands, 2022)
Left ventricular (LV) diastolic dysfunction is one of the important mechanisms responsible for symptoms in patients with heart failure. The aim of the current study was to identify parameters that may be used to detect early signs of LV diastolic dysfunction in diabetic pigs on a high fat diet, using conventional and speckle tracking echocardiography. The study population consisted of 16 healthy Göttingen minipigs and 18 minipigs with experimentally induced metabolic dysfunction. Echocardiography measurements were performed at baseline and 3-month follow-up. The ratio of peak early (E) and late filling velocity (E/A ratio) and the ratio of E and the velocity of the mitral annulus early diastolic wave (E/Em ratio) did not change significantly in both groups. Peak untwisting velocity decreased in the metabolic dysfunction group (− 30.1 ± 18.5 vs. − 23.4 ± 15.5 °/ms) but not in controls (− 38.1 ± 23.6 vs. − 42.2 ± 23.0 °/ms), being significantly different between the groups at the 3-month time point (p < 0.05). In conclusion, whereas E/A ratio and E/Em ratio did not change significantly after 3 months of metabolic dysfunction, peak untwisting velocity was significantly decreased. Hence, peak untwisting velocity may serve as an important marker to detect early changes of LV diastolic dysfunction.